Productivity of a Gasodynamic Loosener - Dyakov, Ivan; Ivkin, Valery (Transport, 2010)
Maximum loads for a semi plane weakened by an aperture under uniform pressure were investigated for elaborating a mechanism for frozen ground destruction applying a recently designed loosener. Recommendations concerning the calculation of loosener productivity depending on the accepted technological scheme are given.First published online: 10 Feb 2011